2022
DOI: 10.1126/science.abn0340
|View full text |Cite
|
Sign up to set email alerts
|

The human oxidation field

Abstract: Hydroxyl (OH) radicals are highly reactive species that can oxidize most pollutant gases. In this study, high concentrations of OH radicals were found when people were exposed to ozone in a climate-controlled chamber. OH concentrations calculated by two methods using measurements of total OH reactivity, speciated alkenes, and oxidation products were consistent with those obtained from a chemically explicit model. Key to establishing this human-induced oxidation field is 6-methyl-5-hepten-2-one (6-MHO), which f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
51
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 56 publications
0
51
0
Order By: Relevance
“…During this time, the bulk of the activity also moved from the kitchen into the living room, nearer to the OH instrument. A recent study has shown that under low O 3 conditions, the surfaces of skin and clothing can act as a radical sink . It is possible that this introduced new heterogeneity in VOC concentrations and radical sinks resulting in a greater loss of OH or any radical precursors nearer the instrument than can be accounted for by the measured VOC concentrations sampled from the kitchen.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During this time, the bulk of the activity also moved from the kitchen into the living room, nearer to the OH instrument. A recent study has shown that under low O 3 conditions, the surfaces of skin and clothing can act as a radical sink . It is possible that this introduced new heterogeneity in VOC concentrations and radical sinks resulting in a greater loss of OH or any radical precursors nearer the instrument than can be accounted for by the measured VOC concentrations sampled from the kitchen.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study has shown that under low O 3 conditions, the surfaces of skin and clothing can act as a radical sink. 41 It is possible that this introduced new heterogeneity in VOC concentrations and radical sinks resulting in a greater loss of OH or any radical precursors nearer the instrument than can be accounted for by the measured VOC concentrations sampled from the kitchen. After people left the house at 17:00, OH returned to its previous concentration of about 6 × 10 6 molecules/cm 3 likely due to the removal of radical sinks adjacent to the instruments.…”
Section: Resultsmentioning
confidence: 99%
“…36,79 Furthermore, a recent study has shown that elevated OH concentrations may form from the ozonolysis of compounds emitted by people. 80 The consequence of these reactions and any potential relative humidity dependence should be investigated by further developing models.…”
Section: Discussionmentioning
confidence: 99%
“…The "atmosphere" of the human body A human-occupied indoor space shares many similarities with Earth and its atmosphere Coralie Schoemaecker 1 and Nicola Carslaw 2 1 Université de Lille, CNRS, UMR 8522-PC2A-Physicochimie des Processus de Combustion et de l'Atmosphère, F-59000 Lille, France 2 Department of Environment and Geography, University of York, York, UK.…”
mentioning
confidence: 99%
“…Less is known about these re-actions on a smaller scale, such as how hu-man-emitted chemicals interact with indoor air. Zannoni et al (2) studied how the human body generates •OH, which may have implications for models such as those used for determining indoor air quality. Understanding the chemistry of indoor air is important as many people spend more time indoors than outdoors, and indoor air quality is a public health concern.…”
mentioning
confidence: 99%